Assessment of contaminants in sand production from petroleum wells offshore Sabah - Shayuti, M.S.M. (Springer Science and Business Media Deutschland GmbH, 2022)
Sand production remains a huge obstacle in many oil and gas fields around the world, but the hazards of contaminants riding on the produced sand are often not emphasised. Improper disposal of the sand could see the toxic leaching into the environment including the food chain, endangering all living organisms. The impending sand production from an oilfield offshore Sabah also suffers from the lack of hazards identification; hence, this study was conducted to assess the contaminant on the produced sand. Sand samples were collected from multiple wells in the area, with the contaminants extracted using n-hexane and subjected to chemical and thermal analyses. FTIR and GCâMS detected traces of harmful pollutants like naphthalene, amine substances, cyclohexanol, and short-chain alkanes. It was discovered that the volatile fraction of the contaminants was able to evaporate at 33Â Â°C, while high energy was needed to remove 100 of the contaminants from the sand. Overall, the produced sand from the oilfield was unsafe and required treatment before it could be dumped or used. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.